Expression of protein arginine methyltransferase‐5 in oral squamous cell carcinoma and its significance in epithelial‐to‐mesenchymal transition. Issue 6 (30th March 2018) - Amano, Yusuke; Matsubara, Daisuke; Yoshimoto, Taichiro; Tamura, Tomoko; Nishino, Hiroshi; Mori, Yoshiyuki; Niki, Toshiro
Abstract : Protein arginine methyltransferases (PRMT) 5, a member of type II arginine methyltransferases, catalyzes the symmetrical dimethylation of arginine residues on histone and non‐histone substrates. Although the overexpression of PRMT5 has been reported in various cancers, its role in oral squamous cell carcinoma (OSCC) has not been elucidated. In the present study, we immunohistochemically examined the expression of PRMT5 in surgically resected oral epithelial dysplasia (OED, n = 8), oral intraepithelial neoplasia (OIN)/carcinoma in situ (CIS) ( n = 11) and OSCC ( n = 52) with or without contiguous OED lesions. In the normal epithelium, PRMT5 was weakly expressed in the cytoplasm of basal layer cells. In OED, OIN/CIS, and OSCC, its expression consistently and uniformly increased in the cytoplasm of dysplastic and cancer cells. Moreover, nuclear and cytoplasmic localization was detected in the invasive front of cancer cells, particularly in cases showing poor differentiation or aggressive invasion patterns. The concomitant nuclear and cytoplasmic expression of PRMT5 correlated with the loss of E‐cadherin and cytokeratin 17, and the upregulation of vimentin, features that are both indicative of epithelial‐to‐mesenchymal transition. PRMT5 may play a role from early oncogenesis through to the progression of OSCC, particularly in the aggressive mode of stromal invasion.